Punca-punca kelewatan pengeluaran perakuan siap dan pematuhan (CCC) projek perumahan di Malaysia - Noraziah Mohammad Zin,; Aishah Samsudin,; Suhana Johar,; Mazlan Mohd Tahir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Certificate of Completion and Compliance (CCC) was implemented in April 2007. The Certificate of Completion and Compliance is a certificate that confirms that a building is eligible and safe to occupy, issued by the main person who submits it. Most of the housing projects fail to hand over the building to the buyer within a set time period such as in the sale and purchase agreement caused by the failure to issue a completion certificate and compliance. This study aims to identify the causes of delays in issuing certificates of completion and compliance for housing projects in Malaysia. Qualitative methods through literature review have been used to identify the processes of issuing certificates of completion and compliance (CCC) of housing projects in Malaysia and to identify the causes of delays in issuing certificates of completion and compliance (CCC). Next, a questionnaire was conducted on 141 respondents to identify the causes of delays in issuing Certificates of Completion and Compliance (CCC) for housing projects in Malaysia. The results of the literacy study found that 18 causes of delay in the issuance of completion and compliance certificates. The findings found that the main contributors to the delay in issuing completion certificates and compliance for housing projects in Malaysia are caused by developers, consultants, contractors, local authorities, external technical agencies and others.